2002
DOI: 10.1161/01.res.0000035254.80718.91
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Enrichment of Cardiomyocytes Derived From Human Embryonic Stem Cells

Abstract: Abstract-Cell replacement therapy is a promising approach for the treatment of cardiac diseases, but is challenged by a limited supply of appropriate cells. We have investigated whether functional cardiomyocytes can be efficiently generated from human embryonic stem (hES) cells. Cardiomyocyte differentiation was evaluated using 3 parent (H1, H7, and H9) hES cell lines and 2 clonal (H9.1 and H9.2) hES cell lines. All cell lines examined differentiated into cardiomyocytes, even after long-term culture (50 passag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
663
4
10

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 835 publications
(707 citation statements)
references
References 47 publications
30
663
4
10
Order By: Relevance
“…Recent extensive developments in the understanding of embryonic stem cells (ESCs) and induced pluripotent stem cells have accelerated cell therapy for bradycardia. Since ESCs have the potential to differentiate into cardiomyocytes, 34,35 transplantation of ESC-derived pacemaker cells induced spontaneous ectopic beats. 36,37 …”
Section: Gene and Cell Therapymentioning
confidence: 99%
“…Recent extensive developments in the understanding of embryonic stem cells (ESCs) and induced pluripotent stem cells have accelerated cell therapy for bradycardia. Since ESCs have the potential to differentiate into cardiomyocytes, 34,35 transplantation of ESC-derived pacemaker cells induced spontaneous ectopic beats. 36,37 …”
Section: Gene and Cell Therapymentioning
confidence: 99%
“…Based on these insights, we suspect that DNA methylation mechanistically contributes to the establishment of an early developmental, undifferentiated phenotype in cancer. It has been widely observed that DNA methyltransferase inhibitors induce differentiation (Xu et al, 2002;Yoon et al, 2006;Banerjee and Bacanamwo, 2010). The hypermethylation of differentiation-associated genes in lung cancer could also provide an explanation for the observed induction of differentiation in cells treated with DNA methyltransferase inhibitors.…”
mentioning
confidence: 95%
“…However, the nervous system and the heart are among the first tissue and organ systems formed from the cells of the ICM in embryogenesis. In fact, substantial neural and cardiac differentiation appears to occur at relatively early stages in embryonic stem cells cultivation under conditions that induce differentiation [2226]. It is deducible that the specification of early embryonic neural and cardiac lineages may occur directly from the pluripotent hESCs, precede the germ layer formation, and subsequently influence lineage determination at later stages of the developmental continuum.…”
Section: Transform Pluripotent Human Embryonic Stem Cells Into Neumentioning
confidence: 99%
“…In hESC-differentiating multi-lineage aggregates (EBs), only a very small fraction of cells (< 4 %) spontaneously differentiate into cardiomyocytes [3,26]. Immune-selection, co-culturing, and morphogens have been used to isolate and enrich populations of immature cardiomyocytes from hESC-differentiating EBs [26,116119]. Enriched hESC-derived cardiomyocytes could generate small grafts and function as the biological pacemaker in animal infarcted models [27].…”
Section: Transform Pluripotent Human Embryonic Stem Cells Into Carmentioning
confidence: 99%
See 1 more Smart Citation